Floridians’ Perceptions of Invasive Species - Nicole M. W. Dodds; Mary Hannah Miller; Alexa J. Lamm (EDIS)
Invasive species are a serious threat in Florida. Invasive species are defined as non-native or exotic organisms, which cause ecological or economic harm or negatively affect human health in a new environment where they are not historically found. This 5-page fact sheet summarizes Florida residents’ perceptions, concerns, and knowledge about invasive species. This information will equip Extension faculty to more effectively communicate and educate clientele on this topic. Written by Nicole M. W. Dodds, Mary Hannah Miller, and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, October 2014.